Analisis Keterampilan Membaca Siswa di Kelas Awal SDN 13 Sungai Pinyuh - Sulipah Sulipah; Yunika Afryaningsih; Dewi Ismu Purwaningsih (CV. Ulil Albab Corp, 2023)
This study aims to analyze the reading skills of students in the early grades of SDN 13 Sungai Pinyuh. This study focuses on the description of students' reading skills in the early grades which refers to how to measure students' reading skills in the early grades using an instrument called EGRA (Early Grade Reading Assessment). The method used in this research is descriptive qualitative. The data source used is the primary data source that has passed the EGRA test. The data collection technique used was the EGRA test. The instrument used is the EGRA test. The data analysis technique used is non-statistical analysis by looking for percentages, then the results are described. Checking the validity of the data findings used is by using the EGRA test which has been proven valid to collect the initial data obtained which is then strengthened by recording student scores from the test results. Based on the results of the research that the researchers have done, the results of students' reading skills in the early grades of SDN 13 Sungai Pinyuh used the EGRA test, namely, 1) aspects of recognizing letters, obtaining an average score of 98.1% and an average score of 100% percentage of success, 2) aspects of reading meaningful words, obtaining an average score of 86.5% and an average percentage score of 89%, 3) aspects of reading meaningless words, obtaining an average score of 80.5% and the average percentage score of success is 89%, 4) aspects of aloud reading fluency and reading comprehension, obtaining an average percentage score of 56% and an average percentage success score of 81.4%. 5) aspects of listening (listening comprehension), obtaining an average percentage score of 70% and an average success percentage score of 92.5%.